Selection and identification of ethanol hiperproducer yeasts from sugar cane molasses - Rodriguez Prado, Macarena (2009)
The decrease of the petroliferous stock and gas in the world, coupled with environmental pollution and global warming, caused mainly by the excessive use of such fuels has generated the need for further studies to become feasible to use new energy sources. The bioethanol consumption produce lower evaporative emissions due to its higher octane concentration and vapor pressure in consequence the pollution levels are much lower than the observed with fossil fuels. The entry into force of Law 26,093 of biofuels in Argentina from 2010 will mean an opportunity for the sugar sector to expand ethanol production to supply 5% of it to all the naphthas. In that regard, Tucumán has a privileged position since its large capacity of ethanol production associated to sugar mills. Our work proposes a microbiological approach to use fermentative microorganisms with high tolerance to alcohol in order to increase ethanol concentration of 11% that is currently obtained in the factories by the alcoholic fermentation of molasses. To take up this, isolation and identification of ethanol hyper-producer strains of yeasts from sugar cane molasses was addressed. Molasses samples were taken from different sugar factories of Tucuman and used to inoculate YPS and YPD media with antibiotics. The microorganisms were inoculated in YPS medium with 50g/L sucrose, incubated at 30ºC with agitation. The fermentations assays were carried out in Erlenmeyers flasks with 200 ml of YPS with 250 g/L of sucrose and incubated at 30 ºC without aeration. Total and direct reducing sugars, biomass and ethanol concentration were determined. Three isolates were selected by your high ethanol production and named as A2, A10 and A11, which produced 11.74, 12.81 and 13.20% of ethanol, respectively. The isolates were identified by sequence analysis of their ARNr 28S intergenic spacer sequences, which allowed assigning identities of 99 and 100% to Saccharomyces cerevisiae. Promising results obtained with isolates A10 and A11 justify further studies leading to an optimization of bioethanol production.